Soil Properties Mediated by Topography Influence Carbon Stocks in a Teak Plantation in the Deciduous Forest Zone of Ghana - Jones Agyei Kumi; Michael Ansong; Winston Asante; Boateng Kyereh (International Journal of Forestry Research)
Recent estimates indicate that over 291 million hectares of the Earth’s land area are occupied by forest plantations, representing 7% of the world’s forest area and 2% of the world’s land area. In Ghana, a substantial amount of degraded land found in hilly areas has been used to establish teak plantations for commercial wood and carbon benefits. Information on the potential influence of topography and soil properties on tree growth and carbon stocks in these plantations is however limited. The study was carried out to assess the influence of elevation on tree growth parameters and carbon stocks in a 7-year-old teak stand and also determined the differences in soil properties along the elevation gradient and its influence on biomass and carbon stocks. Although stand density was statistically similar for the three elevations, tree, diameter, and basal area significantly differed among the three elevations. They were higher at the valley than the mid-slope and the summit. The aboveground biomass and belowground biomass were also significantly higher at the valley compared to the mid-slope and summit. Measured SOC and CEC values between the three elevations showed no significant difference while a positive significant correlation between soil depth and biomass along the altitudinal gradient was observed. Overall, the mean percentage of nitrogen in the soil, pH, potassium, sodium levels, hydrogen, and aluminum varied significantly among the three elevations. Our study suggests that in mountainous areas teak stands in valleys are likely to produce higher biomass and carbon stocks than those in higher elevations; therefore, for better accuracy in biomass and carbon stocks estimations, site elevation should be taken into consideration during carbon stock assessments.